Strategi Manajemen Pembelajaran Melalui Outdoor Education Di Raudlatul Athfal Nurul Hidayah: Learning Management Strategy Through Outdoor Education At Raudlatul Athfal Nurul Hidayah - Nurkhasanah, Siti; Siti Aisyah Sholihah; Fu'ad Arif Noor (EDUCATE : Journal of Education and Culture, 2025)
Early childhood education plays a crucial role in shaping children's physical, social, and cognitive development. One increasingly implemented innovative approach is Outdoor Education, which emphasizes experiential learning in outdoor environments. However, there remains a research gap regarding the implementation of this method in Islamic educational institutions such as Raudlatul Athfal (RA). This study aims to explore learning management strategies through Outdoor Education at RA Nurul Hidayah, covering aspects of planning, implementation, and evaluation. This research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings indicate that RA Nurul Hidayah has implemented curriculum planning strategies based on Outdoor Education, provided necessary facilities, and evaluated learning effectiveness through feedback from teachers, parents, and students. The main supporting factors are school and parental support, while challenges include limited resources and the readiness of educators. In conclusion, Outdoor Education has been proven to enhance children's social skills, motor development, and active participation in learning. Therefore, more systematic planning, teacher training, and collaboration with various stakeholders are needed to optimize the implementation of this method in RA.